A review of research on intercultural learning supported by technology. (November 2020) - Shadiev, Rustam; Sintawati, Wayan
Abstract: The purpose of this study was to review articles on intercultural education supported by technology. We aimed to evaluate the current state of knowledge with respect to (a) employed technology, (b) involved methods, cultures, languages, and participants, (c) arranged learning activities, (d) covered dimensions of the intercultural learning model, and (e) reported problems and their solutions. To this end, twenty-five articles on intercultural learning supported by technology published between 2014 and 2019 were selected and reviewed. The results showed that videoconferencing and email were the most frequently used technologies. Mixed methods were prevalent in the reviewed studies. The countries most frequently involved in intercultural learning were the US and China, and the most frequently used language was English. Most of the studies were conducted among undergraduates and secondary school students. Learning activities followed a similar pattern: (a) self-introduction, (b) culture introduction, and (c) interaction. The dimensions of intercultural learning models were covered in the reviewed articles differently. The two most important dimensions were knowledge and critical cultural awareness. Three main categories of problems were identified; i.e., methodology, learning process, and technology. Based on these results, several conclusions were drawn, and suggestions were provided for future research. Highlights: We reviewed studies on intercultural learning supported by technology. We summarized information from reviewed articles in five dimensions. Implications and suggestions were drawn for educators and researchers.